(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This study examines the effectiveness of Paul Simpson’s Model in analysing James Joyce’s "Ulysses" as a narrative. Ulysses is primarily a dramatic monologue, yet it also functions as a narrative. It tells a complete story, complete with plot, character development, conflict, and setting, all from the king’s point of view. The poem’s narrative aspects make it valuable not just for its poetry but also for its storytelling. Thus, it can be considered a narrative. According to my understanding, Paul Simpson is concerned with this very thing: the question of the relationship between language and ideology; language is a Medium of Ideology, and it bears and transmits ideological meaning. Most importantly, he maintained that language is not more than an expression and reinforcement of social structure and belief. Critical Linguistics and Discourse Analysis, on the other hand, reveal the influence of social and political contexts on language use, the way language shapes itself, and the form of language utterances and written texts, which in turn produce ideology and how language aligns with power relations over social relations.